Kemampuan Paedagogical Content Knowledge (Pck) Calon Guru Pendidikan Biologi FKIP Universitas Muhammadiyah Surakarta Tahun Akademik 2016/2017 Dalam Penyusunan RPP Kurikulum KTSP - Zu'amma, Anis; , Drs. Djumadi, M.Kes (2017)
Teacher as a profession need special skill and should not be done by arbitrary people outside the education. As a professionals, teacher demanded have four competency, one of them namely pedagogical competency. The aim of this study, to know the ability of Paedagogical Content Knowledge (PCK) of biology student prospective teacher. Faculty of Teacher Training and Education Muhammadiyah University of Surakarta 2016/2017 Academic Year in arranging the lesson plan curriculum KTSP. This study used the descriptive qualitative with documentation method. This research population is 126 student of teacher candidate. This sampel research is 56 student of teacher candidate. Technique of this intake sampel research is random sampling. The result of this study shows that the ability CK students teacher candidate namely 69.83% (good). The ability PK 61.66% (sufficient). The ability PCK 75.05%. Conclusion this study namely the ability PCK the biology teacher candidate faculty of teacher training and education Muhammadiyah University of Surakarta 2016/2017 academic year in arraging the lesson plan curriculum KTSP is 75.05% (good). Keyword: PCK, Candidate Teacher, Lesson Plan